Factors Determining the Students’ Choice of Private Management College in Kathmandu - Awale, Sushil (Journal of Management, 2021)
Educational service is one of the most lucrative businesses at present. Nepal is getting tremendous growth in education sector. College managers are not clear why student choose particular college. This study analyzes major factors that determine the students’ choice of Management College in Kathmandu. This study tries to test the effects of convenient location of the college, friends’ choice of college, advertisement, image, past performances, fun, fee, faculties, resource centers and physical environment on choice of college. This study finds image and physical environment of the college only affect significantly in choice of the college.